Today, Tomorrow, and In-Between: Straub/Huillet, the Schoenbergs, and the Gendered Micropolitics of Operatic Performance in Von heute auf morgen. - AMIDON, KEVIN S. (Feminist German Studies)
Artists who have confronted the politics of collaborative theater have been both drawn to and repelled by opera, intrigued by its aesthetic possibilities, its suspect politics, and its economic entanglements. Central to opera's fascination has also been its complex and manifestly gendered production of texts, voices, and performances. This essay explores the 1929 one-act opera Von heute auf morgen by the librettist-composer team of Gertrud and Arnold Schoenberg, and a collaborative filmic performance of it in the 1996 film of the same name by the directorial-production team of Danièle Huillet and Jean-Marie Straub (musical direction by Michael Gielen). These two documents of operatic collaboration, along with the paired intertexts made up of the Straub/Huillet-Gielen film version of Arnold Schoenberg's Moses und Aron (1974-75), interrogate the complex field of attention to reveal its links to the aesthetics of gender, performance, and agency. Thus emerges an essential performative micropolitics embodying potential resistance to the opera's political economy of gendered domination.